2009
DOI: 10.1021/ja8070978
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Rare-metal Absorbing Polymer by Three-component Polyaddition through Combination of Chemo-selective Nucleophilic and Radical Additions

Abstract: Sequential three-component polyaddition has been difficult, because the first addition typically consumes the two reactive monomers to produce a stable intermediate that cannot react smoothly with the remaining most stable monomer. The combination of nucleophilic and radical additions has overcome this thermodynamic problem. The first nucleophilic addition of diamines to cyclic dithiocarbonates produces bis(mercaptothiourethane)s that can attack diethynylbenzene radically, which consequently gives poly(thioure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…Compared with the same concentration of Pd ion, the Pd ion decreased the fluorescence more dramatically than the iron ion because of a property against the oxidative nature of Fe 3+ under acidic conditions and the electro-active nature of polythiophene due to non-acidic conditions. Also, Pd 2+ might interact with sulfur of the PTh shell via chelating or complex reactions [2628]. In addition, complex formation of palladium ion (as a soft acid) with PTh (as a soft base) can be considered as a type of Lewis acid/base (termed as soft acid–soft base reactions) might be a possible description for higher sensitivity of nanoparticles toward palladium ion.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the same concentration of Pd ion, the Pd ion decreased the fluorescence more dramatically than the iron ion because of a property against the oxidative nature of Fe 3+ under acidic conditions and the electro-active nature of polythiophene due to non-acidic conditions. Also, Pd 2+ might interact with sulfur of the PTh shell via chelating or complex reactions [2628]. In addition, complex formation of palladium ion (as a soft acid) with PTh (as a soft base) can be considered as a type of Lewis acid/base (termed as soft acid–soft base reactions) might be a possible description for higher sensitivity of nanoparticles toward palladium ion.…”
Section: Resultsmentioning
confidence: 99%
“…Endo et al reported a metal‐free alkyne‐based MCP of five‐membered cyclic dithiocarbonate 32 , diamine 33 , and diyne 34 , for the preparation of polythiourethane P 15 (Scheme ) . The nucleophilic addition of 32 and 33 first yields a thiol intermediate, which undergoes a radical addition with alkyne.…”
Section: Metal/catalyst‐free Mcpsmentioning
confidence: 99%
“…MCRs have been studied for many years in organic chemistry to prepare numbers of new compounds with potential pharmaceutical properties . In polymer chemistry, MCRs have also been used to prepare new polymers, typical examples are the polycondensates prepared by Yokozawa, Endo and co‐workers, Meier and co‐workers, and Du Prez and co‐workers, etc. Most MCRs are modular, highly efficient, atom economy, and eco‐friendly reactions; thus, two or more functional groups can be easily introduced into the polymer structures leading to the rapid preparation of new multifunctional polymers.…”
Section: Introductionmentioning
confidence: 99%